2005
DOI: 10.2214/ajr.04.1225
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodule Detection with Low-Dose CT of the Lung: Agreement Among Radiologists

Abstract: Unaided intra- and interobserver agreement in detecting pulmonary nodules in low-dose CT of the lung is relatively low. Computer-assisted detection may provide the consistency that is needed for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 34 publications
4
53
1
Order By: Relevance
“…We found that PET had superior interobserver and intraobserver reliability, compared with CT. In addition to the superior performance in characterizing indeterminate lesions, this reliability contributes to the superior accuracy of PET over CT. For characterization of solitary nodules, the interobserver reliability reported here for PET is similar to that previously reported in a smaller series (29), whereas for CT it is better than previously reported (30).…”
Section: Discussionsupporting
confidence: 89%
“…We found that PET had superior interobserver and intraobserver reliability, compared with CT. In addition to the superior performance in characterizing indeterminate lesions, this reliability contributes to the superior accuracy of PET over CT. For characterization of solitary nodules, the interobserver reliability reported here for PET is similar to that previously reported in a smaller series (29), whereas for CT it is better than previously reported (30).…”
Section: Discussionsupporting
confidence: 89%
“…Interobserver variability in reader performance for the detection and characterization of pulmonary nodules has been found to be relatively high with chest computed tomographic (CT) imaging both in the clinical setting and in lung cancer screening (18)(19)(20)(21). So far, the effect of double reading on the cancer detection in lung cancer CT screening has, to our knowledge, not been…”
Section: Study Groupmentioning
confidence: 99%
“…This shows that variability estimates from controlled reader studies may be similar to such estimates from clinical studies, where readers' calls do affect patient outcome. Leader et al (13) examined agreement between readers in nodule detection at CT and showed poor nodule-based interobserver agreement (k = 0.120) but relatively good examination-based interobserver agreement (k = 0.458). A number of other studies (14,15) examined variability across readers in the estimation of lung nodule volume at CT in a controlled setting; NLST radiologists did not assess nodule volume.…”
Section: Disclosures Of Conflicts Of Interest: Pfpmentioning
confidence: 99%